Hormonal, electrolyte disturbances and features of hemostasis in term newborn infants of mothers with gestational diabetes mellitus. - Evgeny Viktorovich Mikhalev; Olga Michailovna Shanina; Tatiana Vladimirovna Saprina (Сахарный диабет, 2015)
The article reviews the available data on investigations in the field of electrolyte (calcium, magnesium), hormonal (insulin, leptin) and hemostasis disturbances in term newborns from women with gestational diabetes; possible mechanisms of their development are also highlighted. The review describes changes in blood glucose concentration in term newborns from women with gestational diabetes, and their impact on the child's condition. In addition to already known factors causing macrosomia and other metabolic disorders in term neonates, the role of leptin (peptide hormone that regulates energy metabolism) is quite discussable. Low leptin levels lead to the development of obesity. It is also confirmed, that leptin influences brain development of the newborn, leading to later cognitive deficits in children from women with GDM. The aim of the review is to summarize the available data on investigations in the field of electrolyte (calcium, magnesium), hormonal (insulin, leptin) and hemostasis disturbances in term newborns from women with gestational diabetes.